2016
DOI: 10.17159/2411-9717/2016/v116n11a2
|View full text |Cite
|
Sign up to set email alerts
|

Review of gold reef sampling and its impact on the mine call factor

Abstract: Sampling error and bias, especially the Increment Preparation Error (IPE), are introduced when the tool allocated to do the job fails to extract a representative sample. This is the case with chip sampling; the tool can only extract haphazard shapes of loose or fractured material and not always from within the demarcated sample area. Increment Extraction Error (IEE) and Increment Delimitation Error (IDE) could be severe, but are found to be relatively unbiased. The uncontrolled action of the sampler in discard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The greatest EE during face sampling arises from differential, hard versus soft rock properties, as a greater quantity of softer material usually enters the sampling bag (Fourie and Minnitt, 2016). If this is high-grade, then the sample will be positively biased, and if low-grade, vice versa.…”
Section: Sample Collection and Methodologymentioning
confidence: 99%
See 4 more Smart Citations
“…The greatest EE during face sampling arises from differential, hard versus soft rock properties, as a greater quantity of softer material usually enters the sampling bag (Fourie and Minnitt, 2016). If this is high-grade, then the sample will be positively biased, and if low-grade, vice versa.…”
Section: Sample Collection and Methodologymentioning
confidence: 99%
“…In a study based on Witwatersrand (RSA) gold mines, Fourie and Minnitt [21] identified an "in-stope sample discard process", where samplers were prone to make a selection of what they believe was better looking material. Such discard of waste and preferential selection of mineralised material leads to a positive "waste discard bias" and hence higher sample assays [21].…”
Section: Sample Collection and Methodologymentioning
confidence: 99%
See 3 more Smart Citations